E01110 DashboardTracking A2 & B4 Enrollment & Completion among Freshmen
CSU Executive Order 1110 called for changes to assessment of academic preparation and placement into A2 (WrittenCommunication GE) and B4 Mathematics/Quantitative Reasoning GE) Courses. Beginning in Fall 2018, these changes were designed ensure students had the opportunity to enroll in credit-bearing A2/B4 courses within their first year rather thanearlier curricular designs which required some students to take 1-2 semesters of non-credit bearing developmental coursesfirst. It also led to changes in support and stretch course offerings to assist students in successful completion of thesegeneral education courses.